Nested PCR for the Diagnosis of Feline Sporotrichosis From Formalin-Fixed and Paraffin-Embedded Samples Using Different DNA Extraction Protocols - Luiz, Raul Leal Faria; Menezes, Rodrigo Caldas; Pereira, Sandro Antonio; Oliveira, Raquel de Vasconcellos Carvalhaes de; Oliveira, Manoel Marques Evangelista (Frontiers in Veterinary Science, 2022)
Sporotrichosis is a chronic, cosmopolitan granulomatous mycosis that affects humans and animals. The infection is caused by the dimorphic fungi Sporothrix sp. The aims of the present study were to evaluate, standardize and validate a nested PCR technique using two DNA purification kits for the extraction of DNA from formalin fixed and paraffin-embedded tissues (FFPE) for Sporothrix sp. detection. FFPE mycological culture pellet samples of different Sporothrix species (S. chilensis, S. mexicana, S. pallida, S. globosa, S. brasiliensis and S. schenckii) were used as positive controls and clinical FFPE tissue samples of animals positive for Cryptococcus sp., Leishmania infantum and Histoplasma sp. were used as negative controls. Ten clinical FFPE skin samples from cats with sporotrichosis were used to validate the nested PCR. These samples were cut into two distinct paraffin sections (5 and 16 µm thick). The paraffin sections were subjected to two different DNA extraction kits (chemical and thermal extractions). A nested PCR was performed on the extracted DNA to identify the genus Sporothrix. The chemical extraction protocol with the 5 µm thick paraffin section was more effective in extracting DNA from Sporothrix sp. from FFPE samples and the nested PCR technique showed the highest sensitivities (100% in the positive controls and of 50% in the skin samples of cats) and specificity (100%). Therefore, the nested PCR using this protocol has great potential to be applied in Sporothrix sp. diagnosis in FFPE samples of cats.